A preparation of homogeneous distribution of palladium nanoparticle on poly (acrylic acid)-functionalized graphene oxide modified electrode for formalin oxidation. (1st September 2017) - Kongkaew, Supatinee; Kanatharana, Proespichaya; Thavarungkul, Panote; Limbut, Warakorn
Graphical abstract: Abstract: An excellent electrocatalytic activity, repeatability and stability of electrochemical sensor for formalin detection was fabricated based on a homogeneous distribution of ellipsoidal palladium nanoparticle (PdNPs) on poly (acrylic acid)-functionalized graphene oxide (PAA-GO) modified on a glassy carbon electrode (GCE) (PdNPs-PAA-GO/GCE) with incorporated flow injection amperometry (FI-Amp). Homogeneous distribution of ellipsoidal palladium nanoparticles (PdNPs) were dispersed on PAA-GO via an electroless deposition method. The surface morphology and electrochemical behavior of the PdNPs-PAA-GO/GCE were characterized by transmission electron microscopy, fourier transform infrared spectroscopy, cyclic voltammetry and amperometry. The PdNPs-PAA-GO/GCE exhibited excellent electrocatalytic activity toward formalin oxidation. Then this modified electrode was incorporated with FI-Amp for formalin sensor development. In order to obtain good analytical performances, many parameters such as the amount of PdNPs-PAA-GO, applied potential, flow rate and sample volume were optimized. Under optimal conditions, this sensor provided a wide linear range, 50-50, 000 μmol L −1, with high sensitivity (320 μA mmol L −1  cm −2 ). The limit of detection and limit of quantitation were 16 μmol L −1 and 53 μmol L −1, respectively. This proposed sensor exhibited good repeatability (RSD < 3.5%), excellence stability (RSD = 1.5%, n = 500) and high sample throughput (60 samples h −1 ). This method was applied to the determination of formalin in soaked fresh food samples with satisfactory recovery.